Role of PCSK9 in the course of ejection fraction change after ST‐segment elevation myocardial infarction: a pilot study - Gema Miñana (ESC Heart Failure, 2020)
Abstract Aims Proprotein convertase subtilisin/kexin type 9 (PCSK9) has emerged as a therapeutic target for reducing plasma low‐density lipoprotein cholesterol. Beyond lipid control, recent findings suggest a deleterious effect of this protein in the pathogenesis of postmyocardial infarction left ventricle remodelling and heart failure‐related complications. The aim of this study was to assess the relationship between circulating PCSK9 and 6 month cardiac magnetic resonance imaging‐derived left ventricular ejection fraction (LVEF) after a first ST‐segment elevation myocardial infarction (STEMI). Methods and results We prospectively evaluated 40 patients with a first STEMI, LVEF < 50% and treated with primary percutaneous coronary intervention in which PCSK9 was measured 24 h postreperfusion. All patients underwent cardiac magnetic resonance imaging 1 week and 6 months after STEMI. Baseline characteristics were compared across median values of PCSK9. The association between PCSK9 levels and LVEF at 6 months was evaluated by analysis of covariance. The mean age of the sample was 60 ± 12 years and 33 (82.5%) were male patients. The infarct location was anterior in 27 patients (67.5%), and 9 patients (22.5%) were Killip class ≥ II. The mean 1 week and 6 month LVEF were 41 ± 7% and 48 ± 10%, respectively. The mean PCSK9 was 1.93 ± 0.38 U/mL. Testing the association between serum PCSK9 and 6 month LVEF with analysis of covariance revealed an inverse relationship (r = −0.35, P = 0.028). After multivariate adjustment, circulating PCSK9 remained significant and inversely associated with 6 month LVEF (P = 0.002). Conclusions In patients with a first STEMI with reduced ejection fraction at index admission and treated with primary percutaneous coronary intervention, circulating PCSK9 was associated with lower LVEF at 6 months.